2021
DOI: 10.1093/ajhp/zxab051
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and secondary traumatic stress in health-system pharmacists during the COVID-19 pandemic

Abstract: Purpose To describe the prevalence of burnout and secondary traumatic stress (STS) in health-system pharmacists during the coronavirus disease 2019 (COVID-19) pandemic. Methods. A cross-sectional, professional pharmacy organization listserver–based online survey of a target group of health-system pharmacists across the United States was conducted. The survey was sent out through professional organization listservers and was anonymous and voluntary. The survey questionnaire i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 18 publications
0
68
0
1
Order By: Relevance
“…A recent study using the Maslach Burnout Inventory reported high burnout levels, specifically, 25% for emotional exhaustion, 34.9% for depersonalization, and 3% for personal accomplishment [37]. The phenomenon of high burnout among healthcare workers during stressful events has been reported in several recent studies around the world [38,39]. A significant proportion of pharmacists reported increased workload, decreased income, and less safe environment.…”
Section: Discussionmentioning
confidence: 96%
“…A recent study using the Maslach Burnout Inventory reported high burnout levels, specifically, 25% for emotional exhaustion, 34.9% for depersonalization, and 3% for personal accomplishment [37]. The phenomenon of high burnout among healthcare workers during stressful events has been reported in several recent studies around the world [38,39]. A significant proportion of pharmacists reported increased workload, decreased income, and less safe environment.…”
Section: Discussionmentioning
confidence: 96%
“…A study among community pharmacists in France found that up to 35% of pharmacists reported psychological disturbances, including burnout ( Lange et al 2020 ). Another study in the USA reported that burnout affected more than half of healthcare pharmacists ( Jones et al 2021 ).…”
Section: Textmentioning
confidence: 99%
“…Additionally, the effect of attending university during a pandemic should be studied to address potential mental health implications in young pharmacists. 19…”
Section: Discussionmentioning
confidence: 99%